(3SjchdhLjI GdGOGQI GdQjGVjIs - (3HGgj eUWai MSjfs; (3eMeO eJhdj Yajaj s ((3GdbGgQIs (3ecJHI GdCfLdh GdeUQjIs, 2005)
(3JYQV dJWhQ fXQjGJ GdGOGQI h RjGOI eYOd GdJWhQ GdJcfhdhLj h XghQ eTcdGJ YOjOI JMGhd GdJUOj dgG efgG GdGOGQI h GdVZhW aj GdeDSSGJ GdGLJeGYjI hGdQjGVI hGOGQI GdUQGY aj GdefXeGJ GdQjGVjI ,h cja fhGLgg h fbdU ef fJGFLg GdSdHjI(B.s
Keywords: (3GdJQHjI GdHOfjI(B_(3GdeQGab GdQjGVjI(B_(3GOGQIs